2022
DOI: 10.1172/jci156768
|View full text |Cite
|
Sign up to set email alerts
|

Human midbrain dopaminergic neuronal differentiation markers predict cell therapy outcomes in a Parkinson’s disease model

Abstract: Human pluripotent stem cell–based (hPSC-based) replacement therapy holds great promise for the treatment of Parkinson’s disease (PD). However, the heterogeneity of hPSC-derived donor cells and the low yield of midbrain dopaminergic (mDA) neurons after transplantation hinder its broad clinical application. Here, we have characterized the single-cell molecular landscape during mDA neuron differentiation. We found that this process recapitulated the development of multiple but adjacent fetal brain regions includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 64 publications
2
16
0
Order By: Relevance
“…6C and Table S3). Moreover, GSEA identified novel neurogenesis-related genes in hFP-Rgl1 previously shown to enrich for mDA progenitors, including TPBG and PTPRO (Xu et al, 2022; Yoo et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…6C and Table S3). Moreover, GSEA identified novel neurogenesis-related genes in hFP-Rgl1 previously shown to enrich for mDA progenitors, including TPBG and PTPRO (Xu et al, 2022; Yoo et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…We show that ST introduces less bias in cell type composition compared to scRNA-seq. 35 , 36 This is most likely because there is no tissue dissociation before cDNA synthesis, leading to an equal likelihood of capture for most cell types. This is especially obvious when looking at the vulnerable cell types, such as neurons, which become dwarfed by the glial cell numbers in scRNA-seq.…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 33 , 34 This approach, however, leaves the transplant’s final composition challenging to predict and control. 35 The final graft composition in vivo from hESC-derived dopaminergic transplants has been analyzed in bulk 36 and at single-cell resolution. 18 However, the quantitative results of the latter study were at odds with histological assessments since the sequencing study suggested that neurons make up the minority of the transplant.…”
Section: Introductionmentioning
confidence: 99%
“…Clusters were annotated based on the expression of known markers identified from several literatures. DA progenitors were annotated for their highly expressed markers such as NEUROG2, NHLH1 and SOX4 [29,30]. DA-0 was annotated based on the high expression of ErbB4 known to be expressed in DA neurons and low level of SYT1 a post-synaptic marker [31].…”
Section: Clustering and Cell Type Annotationsmentioning
confidence: 99%